Global Outbreaks of SARS-nCoV-2 (COVID-19 Pandemic) and Spread out in Bangladesh - Hossain, Md Belal (Bangladesh Journal of Infectious Diseases, 2020)
Currently, the world is concerned about the 2019 novel CoV (SARS-nCoV-2), the disease it causes has been named “coronavirus disease 2019” (COVID-19) that was initially identified in Wuhan, China on 31 December 2019. Infected patients presented with severe viral pneumonia and respiratory illness. The new SARS-CoV-2 is RNA genomes and a beta-coronavirus, like SARS-CoV and MERS-CoV. In this article, provide a brief insights into past and present outbreaks of COVID-19. At end of the April 2020, COVID-19 Pandemic spread out all over the world in 210 countries/areas and the number of confirmed cases has been mounting globally. Reported in USA alone, over one million people are infected which is one-third of world confirmed cases and deaths cases also near to one-fourth of the total estimated deaths cases so far recorded globally. In other countries of the world situation is almost same but in Europe COVID-19 positive cases so high including death cases. In Bangladesh, the number of confirmed cases and fatality rate is lower than other reported countries in the world, due to deficient testing facilities and inadequate number of samples are tested, the virus seems to be highly contagious in Bangladesh as well. Although the fatality rate of SARS-nCoV-2 is currently lower than SARS-CoV and MERS-CoV, but the virus seems to be highly contagious based on the number of infected cases to date. Bangladesh Journal of Infectious Diseases 2020;7(1):38-41